Cinematic Mechanisms of Immersive Experience in Kapur’s Elizabeth Duology - Nayla Sabrina; Hasbi Assiddiqi; Dian Nurrachman (Jayapangus Press, 2026)
This research investigates the deployment of cinematic discourse mechanisms in Shekhar Kapur's Elizabeth duology as vehicles for constructing an immersive audience experience of Queen Elizabeth I's psychological transformation. Drawing on Chatman's story-discourse framework as its primary analytical lens, the study examines how Elizabeth (1998) and Elizabeth: The Golden Age (2007) systematically employ medium-specific techniques cinematography, editing, sound design, and mise-en-scène to position spectators as active experiential participants rather than detached observers of historical biography. Qualitative formalist analysis of key transformation sequences demonstrates that the psychological impact of both films derives not from their historical subject matter but from a coordinated orchestration of formal strategies engineered to produce perceptual alignment, emotional mirroring, and subjective spectatorship. Significantly, the deliberate narrative discontinuities between the two films emerge as sophisticated discourse mechanisms in their own right, formally enacting the dissociation inherent in sovereign identity formation and compelling audiences to undertake the same cognitive labor as Elizabeth's own psychological reconstruction. By integrating Smith's character engagement theory, Bordwell and Thompson's account of classical film technique, and Plantinga's embodied spectatorship model, the study establishes that Kapur's duology redefines the conventions of biographical cinema, converting historical representation into phenomenological encounter. The conclusion affirms cinema's singular capacity to generate experiential comprehension of complex psychological processes through deliberate formal manipulation, and offers a transferable methodological framework for analyzing discourse-driven narratives across historical and biographical film genres.